Surveillance of Multidrug-Resistant Genes in Clinically Significant Gram-Negative Bacteria Isolated from Hospital Wastewater - Shriya C. Shetty; Lakshya S. Gowda; Ankeeta Menona Jacob; Kalidas Shetty; A. Veena Shetty (Antibiotics, 2025)
Background/Objectives: Antimicrobial resistance (AMR) has become a serious public health threat worldwide. Among the various surveillance domains, hospital wastewater (HWW) has been overlooked, and it is the major reason for the threats posed by AMR. Therefore, the HWW domain is of paramount importance for tackling the AMR. In this regard, the present study investigated the occurrence of Gram-negative bacteria from HWW and evaluated the isolates’ multi-drug-resistant (MDR) pattern in the study environment. Methods: This descriptive study involves HWW samples (n = 24) consecutively collected across 6 months. The samples were cultured for bacteria, identified, and subjected to antimicrobial susceptibility testing via Kirby–Bauer. PCR confirmed the presence of drug-resistance genes in Gram-negative bacterial isolates. Results: High rates of Enterobacterales resistant to carbapenems and cephalosporins observed in isolates from final treated effluent. The molecular screening showed tetD, tetE, tetG, catA1, catA2, blaNDM-1, quinolones, qnrA, qnrB, qnrS, and qepa. Conclusions: Overall, our results suggest that microbiological surveillance and identification of resistance genes of clinically important pathogens in HWW can be a general screening method for early determination of under-detected antimicrobial resistance profiles in hospitals and early warning of outbreaks and difficult-to-treat infections.